SAT0170 Work-Related Disability in Behcet'S Syndrome: A British Series. (23rd January 2014) - Mehta, P.; Ambrose, N.; Haskard, D.
Abstract : Background: Behcet's syndrome (BS) is a rare, heterogenous inflammatory disorder which is most active during working years, thus affecting productivity. Objectives: We aim to survey the frequency of and reasons for work-related disability among patients attending our tertiary referral BS centre and also how work may affect patients' health with respect to their Behcet's syndrome. Methods: The proposal was discussed with the Behcet's syndrome society patient group and approval was obtained from the Research Ethics committee. A postal questionnaire survey was sent to 200 patients attending our BS clinic. Consent was implied, by return of questionnaires. Results: 70 responses were received. 46% were male. The median age was 47 years. 78% were White British. 42% had high-school education, 31% university degrees and 16% vocational qualifications. 7% considered themselves to have significant co-morbidities. 19% were taking no medication, 49% steroids, 61% immunosuppressants and 17% TNF-blockers. 13% were homemakers, 21% retired (73% medically retired), 3% students, 54% employed and 9% unemployed. 81% of the 32 patients currently not working, had been working before BS was diagnosed. 84% of these patients stated they were not working because of BS. The most common reasons for this oral ulceration and the effects on speech (42%) and fatigue (29%). 31% patients felt their BS had improved after stopping work. Of the 54% working, 61% were full-time and 39% part-time. 53% had made changes to their work because of BS – reduced hours (43%), part-time work (32%) and changed job (25%). 65% felt their BS had improved after these changes. The mean number of sick days was 18, with 13 days attributed to BS. The mean visual analogue scale assessments for the effect of BS on productivity at work was 7, the effect of BS on regular activities was 4 and the effect of work on BS was 6. Conclusions: Work-related disability in BS is high and underappreciated. A large number of patients give up work or change their work practice because of BS, particularly the effects of oral ulceration on speech. The perceived effects of BS on productivity at work and the effects of work on patients' health are considerable. Disclosure of Interest: None Declared